Pengaruh Penerapan Metode Demonstrasi dan Motivasi Belajar Terhadap Kemampuan Membaca Al-Qur`an Secara Tartil Siswa SMA Islam Al-Azhar 5 Kota Cirebon - Isyraq Fauziyyah (Misykah : Jurnal Pemikiran dan Studi Islam, 2021)
This thesis examines the effect of the application of the demonstration method and learning motivation on the students' ability to read the Qur'an in Tartan Islamic high school Al-Azhar 5 Cirebon City. This research is a descriptive quantitative research. a balance between: a) Human relations with Allah SWT b) Human relations with fellow humans c) Human relations with oneself d) Human relations with other creatures and their environment. The scope of Islamic Religious Education subject matter includes five main elements, namely: a) al-Qur'an b) Aqidah c) Shari'ah d) Morals e) Date. In this research, the writer will focus on learning Al-Qur'an education using demonstration method. This has the aim that by implementing the demonstration method in learning al-Qur'an education, it can improve the ability of students to read the al-Qur'an. To achieve the maximum learning goals and objectives, a good delivery method is needed, which is commonly called a method. Respondents' responses regarding the use of the demonstration method in the Al-Qur`an Education subject were sufficient. This is evident from the average results of the application of the demonstration method, most of which are in the good category with an average percentage of achievement of 78.75% because it is in the 75% - 100% interval. As for the relationship between the application of the demonstration method in increasing learning motivation and the ability to read Al-Qur`an in tartile manner at AL-Azhar 5 Senior High School in Cirebon, there is a moderate correlation. This can be proven from the calculation of the correlation coefficient with a value of 0.696 which is in the range 0.40-0.70. The magnitude of the influence of the demonstration method on tartiles was 48.44%, while the remaining 51.56% was influenced by other factors not examined. Demonstration method was found to significantly improve artillery because the "r" product moment is at the 95% significance level is 0.374 and at the 99% significance level is 0.478. Because robservation "ro" is greater than "rtabel" "rt", either at the 95% significance level (0.69> 0.374) or (0.69> 0.478), it is Ha which states that there is a significant positive correlation between the Demonstration Method in increasing motivation to learn to read Al-Qur`an in tartile manner at Al-Azhar 5 High School Cirebon City was accepted. Whereas Ho, who stated that there was no significant positive correlation between the Demonstration Method in improving the tartile way of reading Al-Qur`an at Al-Azhar 5 High School in Cirebon, was rejected. Abstrak Tesis ini mengkaji tentang Pengaruh Penerapan Metode Demonstrasi Dan Motivasi Belajar Terhadap Kemampuan Membaca Al-Qur`An Secara Tartil Siswa SMA Islam Al-Azhar 5 Kota Cirebon Penelitian ini merupakan penelitian deskriptif kuantitatif.penelitian ini menggunakan ruang lingkup Pendidikan Agama Islam meliputi keserasian, keselarasan dan keseimbangan antara: a) Hubungan manusia dengan Allah SWT b) Hubungan manusia dengan sesama manusia c) Hubungan manusia dengan dirinya sendiri d) Hubungan manusia dengan makhluk lain dan lingkungannya. Adapun ruang lingkup bahan pelajaran Pendidikan Agama Islam meliputi lima unsur pokok, yaitu: a) al-Qur’an b) Aqidah c) Syari’ah d) Akhlak e) Tarikh. Dalam penelitian ini penulis akan mefokuskan pada pembelajaran pendidikan al-Qur’an dengan menggunakan metode demonstrasi. Hal tersebut mempunyai tujuan bahwa dengan diterapkannya metode demonstrasi dalam pembelajaran pendidikan al-Qur’an dapat meningkatkan kemampuan peserta didik dalam membaca al-Qur’an. Untuk mencapai maksud dan tujuan pembelajaran yang maksimal diperlukan cara penyampaian yang baik, yang biasa disebut dengan metode. Tanggapan responden tentang penggunaan metode demontrasi pada mata pelajaran Pendidikan Al-Qur`an sudah cukup. Hal ini terbukti dari hasil rata-rata pencapian penerapan metode demontrasi yang sebagian besar berada pada kategori baik dengan rata-rata prosentase pencapaian sebesar78,75 % karena berada pada interval 75 %- 100 %. Adapun hubungan antara penerapan metode demonstrasi dalam meningkatkan motivasi belajar dan kemampuan cara membaca Al-Qur`an secara tartil di SMAI AL-Azhar 5 Kota Cirebon terdapat korelasi sedang. Hal ini dapat dibuktikan dari perhitungan koefisien korelasi dengan nilai 0,696 yang berada pada rentang 0,40-0,70. Besaran pengaruh metode demontsrasi terhadap tartil 48,44% sedangkan sisanya 51,56 % dipengaruhi oleh faktor lain yang tidak diteliti. Metode Demontrasi ternyata secara signifikan meningkatkan ketartilan karena “r” product moment berada pada taraf signifikansi 95 % adalah 0,374 dan pada taraf signifikansi 99 % adalah 0,478 . Karena robservasi “ro” lebih besar dari “rtabel” “rt” ,baik pada taraf signifikansi 95 % (0,69> 0,374) ataupun (0,69> 0,478), maka Ha yang menyatakan bahwa terdapat korelasi positif yang signifikan antara Metode Demontrasi dalam meningkatkan motivasi belajar membaca Al-Qur`an secara tartil di SMAI Al-Azhar 5 Kota Cirebon diterima. Sedangkan Ho yang menyatakan bahwa tidak terdapat korelasi positif yang signifikan antara Metode Demontrasi dalam meningkatkan cara membaca Al-Qur`an secara tartil di SMAI Al-Azhar 5 Kota Cirebon ditolak.